Atomic Insight Into Phase Transition Lowering in Shock Compressed Copper - Ling , Weidong; Chen, Bo; Zeng , Qiyu; Yu , Xiaoxiang; Zhang , Shen; Zhao , Zengxiu; Dai, Jiayu (Frontiers in Physics, 2022)
High pressure structural transformation of copper (Cu) is a rather complex physical process. One of the intriguing questions that are rarely discussed is the comparison between quasi-isentropic and adiabatic response for copper lattice transition. The ambient face-centered-cubic (FCC) structure of Cu is predicted to persevere over 100 TPa from ab inito calculations, and experimentally demonstrated to persist until 1.15 TPa in ramp compression and 150 GPa in static compression. However, a novel body-centered-cubic (BCC) order is observed merely at 180 GPa once shock compression is applied. The mechanism of BCC phase transition occurred at low pressure under shock compression remains elusive so far and much attention is required on the dynamics in such phase transition. In this work, we utilize molecular dynamics method to simulate the shock compression on copper lattice to uncover the structural transition in atomic scale. We report the FCC-BCC phase transition occurred at 156 GPa and lots of disordered structures are discovered in BCC phase after impact, revealed by a series of structure analysis tools and free energy calculations. The plethora of transient disordered structures reduces the global Gibbs free energies thus leading to the downgrade of the transition pressure in contrast to the ramp and static compression, which provides a new perspective for structural transformation under extreme conditions.